Exome Sequencing: Mutilating Sensory Neuropathy with Spastic Paraplegia due to a Mutation in FAM134B Gene. (12th December 2018) - Wakil, Salma M.; Monies, Dorota; Hagos, Samya; Al-Ajlan, Fahad; Finsterer, Josef; Al Qahtani, Aisha; Ramzan, Khushnooda; Al Humaidy, Rawan; Al-Muhaizea, Mohamed A.; Meyer, Brian; Bohlega, Saeed A.
Abstract : Hereditary sensory and autonomic neuropathies (HSANs) are a clinically and genetically heterogeneous group of disorders involving various sensory and autonomic dysfunctions. The most common symptoms of HSANs include loss of sensations of pain and temperature that frequently lead to chronic ulcerations in the feet and hands of the patient. In this case study, we present the clinical features and genetic characteristics of two affected individuals from two unrelated Saudi families presenting mutilating sensory loss and spastic paraplegia. We employed homozygosity mapping and exome sequencing which is an efficient strategy to characterize the recessive genes, thus obtaining a rapid molecular diagnosis for genetically heterogeneous disorders like HSAN. Subsequently, a nonsense mutation (c.926 C>G; p.S309⁎ ) in FAM134B was identified. In addition, we confirmed that the mutant FAM134B transcripts were reduced in these patients presumably disrupting the receptors of the degradative endoplasmic reticulum pathways that facilitate the autophagy processes.